Enhancing functional balance in stroke survivors with very severe motor impairment through core exercise - Zuliana Bacho; D. Maryama Ag Daud; Khin Nyein Yin (Springer Nature, 2024)
Stroke survivors with severe motor impairment often struggle to maintain balance and posture due to issues such as body imbalance and asymmetric posture. Core exercise interventions have emerged as a potential solution to enhance functional outcomes. This study aimed to assess the impact of a 12-week core exercise program on functional balance and walking ability among stroke survivors with profound motor deficits. Participants meeting specific criteria engaged in a core exercise regimen spanning four progressive levels targeting core muscle groups. Functional balance evaluated using the Brunel Balance Assessment (BBA) at baseline and weeks 2, 4, 6, 8, 10, and 12, exhibited remarkable improvements over the 12- week period (x2 (6) = 54.125, p < 0.0001). This progress indicated enhanced dynamic standing ability and improved base of support adjustment. Notably, the intervention led to a substantial average increase of 4 BBA levels, yielding an effect size of 1.35, signifying a substantial impact. The findings underscore the transformative potential of core exercise interventions on functional balance in stroke survivors with severe motor impairment. These enhancements align with neuroplasticity theory, showcasing the adaptability of the nervous system through targeted interventions that enhance core muscle function, strength, and control. Incorporating core exercise interventions into stroke rehabilitation protocols is paramount, as emphasized by the study’s results. Future endeavors should explore larger, randomized controlled trials with extended follow-up periods to optimize core exercise strategies within stroke rehabilitation. Ultimately, these interventions hold promise for elevating the quality of life and functional outcomes of stroke survivors grappling with considerable motor deficits. Top of Form.